Glucose Control Has an Impact on Cerebral Blood Flow Alterations in Chronic Tinnitus Patients - Xia, Wenqing; Cui, Jinluan; Luo, Yong; Xu, Jin-Jing; Chen, Huiyou; Yin, Xindao; Ma, Jianhua; Wu, Yuanqing (Frontiers in Neuroscience, 2021)
Purpose: Both tinnitus and type 2 diabetes mellitus (T2DM) are linked with cognitive decline and brain dis-functioning. This study used arterial spin labeling (ASL) perfusion functional magnetic resonance imaging (fMRI) to examine the abnormal cerebral blood flow (CBF) patterns existed in tinnitus patients and potential relationships between the abnormal CBF and cognitive performance. The impact of T2DM on CBF alterations in tinnitus patients was further explored. Methods: Sixty tinnitus patients and 40 non-tinnitus subjects were recruited. CBF images were collected and analyzed using ASL perfusion fMRI. Brain regions with CBF alterations between tinnitus patients and non-tinnitus controls were identified by one-way ANOVA. Interaction effects between tinnitus and T2DM for CBF changes were also selected. Then, correlation analyses were calculated to specify the link between CBF changes and cognitive performance and between CBF changes and diabetic characteristics. Results: Tinnitus patients showed decreased CBF, primarily in the auditory area and default mode network (DMN) compared with non-tinnitus controls. Decreased CBF in these regions was correlated with executive function and attention. The interaction effect between tinnitus and T2DM was significant in the right medial prefrontal gyrus. Additionally, CBF in the right medial prefrontal gyrus was correlated tinnitus distress and cognitive performance. In tinnitus patients, Hemoglobin A1c was associated with CBF in the right medial prefrontal gyrus. Conclusions: Tinnitus affects brain perfusion in the auditory area and DMN. T2DM and uncontrolled glucose levels may aggravate a CBF decrease in tinnitus patients. These new findings implied that tinnitus patients may benefit from blood glucose control in terms of their cognitive function and tinnitus distress.